Beta‐lactam allergies, surgical site infections, and prophylaxis in solid organ transplant recipients at a single center: A retrospective cohort study. Issue 5 (18th October 2022) - Mowrer, Clayton; Lyden, Elizabeth; Matthews, Stephen; Abbas, Anum; Bergman, Scott; Alexander, Bryan T.; Van Schooneveld, Trevor C.; Stohs, Erica J.
Abstract: Background: Beta‐lactam allergies (BLAs) are common in hospitalized patients, including transplant recipients. BLA is associated with decreased use of preferred surgical site infection (SSI) prophylaxis and increased SSIs, but this has not been studied in the transplant population. Methods: We reviewed adult heart, kidney, and liver transplant recipients between January 1, 2016 and December 31, 2019 to characterize reported BLA and collect SSI prophylaxis regimens at time of transplant. We compared the use of preferred SSI prophylaxis and SSI incidence based on reported BLA status. Post hoc we collected antibiotic days of therapy (DOT) (excluding pneumocystis prophylaxis) in the 30‐day period posttransplant for patients without SSI. We utilized descriptive statistics for comparisons. Results: Of 691 patients included (116 heart, 400 kidney, and 175 liver transplant recipients), 118 (17%) reported BLA. Rash and hives were the two most reported BLA reactions (36% and 24%), categorized as potential T‐cell mediated and IgE mediated, respectively. Preferred SSI prophylaxis was prescribed in 13 (11%) patients with BLA and 573 (92%) without BLA ( p < .001). No difference could be detected in SSI incidence between BLA and non‐BLA patients (4.2 vs. 4.3%, p = 1.0). Of 659 without SSI, 169 (25.6%) received antibiotics within 30 days of transplant; mean antibiotic DOT for BLA and non‐BLA patients were 3.5 ± 8.0 versus 2.3 ± 5.8, p = .12. Conclusion: BLA transplant recipients received nonpreferred SSI prophylaxis more frequently than non‐BLA recipients, but there was no difference in 30‐day SSIs between the groups. One‐fourth of solid organ transplant recipients received systemic antibiotics within 30 days of transplant. Abstract : Graphical abstract: